The transcending power of goods: Imaginative value in the economy - Jens Beckert (Max Planck Institute for the Study of Societies, 2010)
What do we value? For markets to operate and for economies to grow, producers must attract purchasers to the products they offer. In advanced capitalist economies, market saturation and decline of demand are constant threats to markets. But how do we understand why actors desire the things whose value they reveal in the purchase? In this article I distinguish between three types of value: Physical value, positional value and imaginative value. Based on Durkheim's sociology of religion, I argue that imaginative value emerges from the imaginative connections made between goods and socially rooted values, as well as the aesthetic ideals held by the purchaser. The article explores how the connection between objects and their symbolic meaning is created and maintained, and why the symbolic valuation of objects changes. By arguing that the imaginative value of goods is closely linked to social values, I suggest that consumption is not the expression of a hedonistic individualism but inherently connected to the social and moral order of society. Durkheim's sociology of religion is thus read as a sociology of valuation. – – Was schätzen wir wert? Märkte und wirtschaftliches Wachstum hängen davon ab, dass Verkäufer mit den angebotenen Produkten Käufer anziehen. In entwickelten kapitalistischen Ökonomien sind Markterschöpfung und der Rückgang von Nachfrage immerwährende Bedrohungen von Märkten. Wie aber können wir verstehen, weshalb Akteure die Waren begehren, deren Wert sie mit dem Kauf anzeigen? Der Aufsatz unterscheidet zwischen drei Typen von Wert, dem physischen, positionalen und imaginativen Wert. Ausgehend von Durkheims Religionssoziologie wird argumentiert, dass Wert auch in der imaginativen Verbindung zwischen Gütern und sozialen Werten sowie den ästhetischen Idealen der Käufer entsteht. Es wird untersucht, wie diese Verbindung zwischen Objekten und ihren symbolischen Bedeutungen entsteht und aufrechterhalten bleibt und warum sich der symbolische Wert von Gütern verändert. Wenn der imaginative Wert von Gütern eng mit sozialen Werten verknüpft wird, ist Konsum nicht Ausdruck eines hedonistischen Individualismus, sondern steht in Zusammenhang mit der moralischen Ordnung der Gesellschaft. Durkheims Religionssoziologie wird so als Soziologie des Werts gelesen.
Keywords: 300; Konsumentenverhalten; Soziale Werte; Sozialpsychologie; Religion; Soziologie